UP TO DATE INFORMATION FOR LEADING CARDIOLOGISTS AND THERAPEUTISTS ABOUT LATEST PREVENTION AND THERAPY METHODS REDUCES GROWTH RATE OF CARDIOVASCULAR DISEASES - E. Aleeva (Рациональная фармакотерапия в кардиологии)
Up to date information for leading cardiologists and therapeutists about latest prevention and therapy methods reduces growth rate of cardiovascular diseases.